2020
DOI: 10.1111/bjop.12484
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a ‘pretend play‐based training’ designed to promote the development of emotion comprehension, emotion regulation, and prosocial behaviour in 5‐ to 6‐year‐old Swiss children

Abstract: The objective of this study was to evaluate the effects of a pretend play‐based training designed to promote the development of socio‐emotional competences. 79 children aged 5 to 6 years were evaluated before and after a pretend play‐based training. The experimental group (39 children) received this programme on emotion comprehension, negative emotion regulation, and prosocial behaviour one hour a week for eleven weeks during class hours, while the control group (40 children) received no specific intervention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 70 publications
(91 reference statements)
1
17
0
1
Order By: Relevance
“…Indeed, they support the idea that it is essential to provide a pedagogical structure adapted to the way children learn at the beginning of school through two means. The first is giving a privileged status to “play” (such as constructing play, make believe play, and locomotor play), that fosters relational opportunities with peers, allows for the reinvestment, experimentation and consolidation of knowledge such as numerical abilities, social-emotional competences 61 , and gives an essential place for movement. The second means is providing teaching time centred on these different specific abilities and forms of knowledge inside and outside these moments of play.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, they support the idea that it is essential to provide a pedagogical structure adapted to the way children learn at the beginning of school through two means. The first is giving a privileged status to “play” (such as constructing play, make believe play, and locomotor play), that fosters relational opportunities with peers, allows for the reinvestment, experimentation and consolidation of knowledge such as numerical abilities, social-emotional competences 61 , and gives an essential place for movement. The second means is providing teaching time centred on these different specific abilities and forms of knowledge inside and outside these moments of play.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there is growing evidence in the existing literature of correlational and interventional studies demonstrating the benefits of this form of play for children’s cognitive and socio-emotional development. For example, in a recent interventional study, Richard, Baud-Bovy, Clerc-Georgy, and Gentaz (2021) [ 55 ] showed an improvement in children’s ability to recognize emotions and associate facial expressions of emotion to the correct emotional label in 5- to 6-year-old children. Five teachers implemented a program based on pretend-play, including structured teaching/learning periods centered on socio-emotional competencies (e. g., discussions with the whole group of children on how to recognize basic emotions).…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, the emotion triggered by a situation (e.g., a critique that makes one sad) is then increased because of a deeper cause (e.g., several weeks of harassment). In this context, research has underlined the benefits of various educational programs (e.g., [ 12 , 32 , 33 ]) that focus on a better understanding of how emotions work, and include training that allows children to learn to link situations and emotions by confronting their point of view with those of others.…”
Section: Classroom Aims: Emotional Competencies In English Classesmentioning
confidence: 99%
“…A crucial point may be to create a supportive classroom environment by setting clear rules (and enforcing them) in particular exercises. Non-violent communication and the expression of positive emotions of gratitude are easier to implement, and work towards the installation of harmonious social relationships and an optimal classroom climate (e.g., [ 33 , 34 ])): The students are able to express gratitude to someone who helped them or to write a heartfelt message of gratitude to a loved one (e.g., [ 40 ]); The students are able to create an appropriate response, using the principles of non-violent communication [ 34 ], for the person who broke their phone (see Figure 1 ). …”
Section: Pedagogical Sequencementioning
confidence: 99%